TRUST DALAM IMPLEMENTASI KEBIJAKAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI KABUPATEN SLEMAN - AFRISAL, ADE FERRY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Trust in the implementation of public policy plays an important role as one of the key factors that determine the success of a public policy. This research aims to analyze trust in public policy implementation, in this case Land and Building Tax in Sleman Regency. Moreover, it also analyzes the implementation of selfassessment system in tax policy. This research which taken place in Sleman applies the qualitative research method. Data in this research was obtained through desk-research and by interviews, with selected informants based on purposive sampling. Based on this research the author discovered that trust in public policy implementation of land and building tax is not given directly by the policy makers, rather through policy that is being regulated in the law by self-assessment system. Such trust is risky because it can easily be abused. This then becomes the main factor that makes self-assessment system not working properly. Trust given in these policies can be categorized as encapsulated trust, which is a trust given by consideration and interests encapsulated in a policy and not directly given by the policy makers. In order to increase the level of trust in collecting land and building tax, what need to be done are through public participation in policy making, to prevent imbalance of information between tax authorities and taxpayers, good public services, and the law enforcement through giving strict sanctions to ensure that the trust given can still run well, even thought is a forced trust.